Hipokrit Indonesia Sebuah Kajian Perbandingan Sifat Manusia Indonesia Terhadap Keagamaan - Fadhilah Sabrina; Umi Miftachur Rohmah; Fisca Dwiyanti; Amanda Novia Anwar; Ade Suryanda (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Hypocrite in the Big Indonesian Dictionary is defined as a hypocrite or someone who likes to pretend. Therefore, a hypocritical country can be defined as a country that often pretends and is not serious in carrying out its duties. The constitution stipulates firmly that the State of Indonesia is a legal state. Several experts have developed a definition of the rule of law which can briefly be interpreted as the government's power to protect its citizens from arbitrariness and guarantee protection, guarantees and respect for human rights. However, this is different from the promise of the Indonesian constitution regarding the rule of law. The government guarantees the protection of citizens by taking policies that are contrary to the wishes of the people and also the ideals of the rule of law. Not only the government but the attitude of the Indonesian people also supports that Indonesia is the most hypocritical/hypocritical country. Things that must be improved to avoid hypocrisy itself are by prioritizing or improving education in Indonesia. Therefore, this research focuses on what things make Indonesia the most hypocritical country. The method used is literature study and written interviews via questionnaires with a qualitative descriptive research type. The expected result of this research is to make the Indonesian people aware that the Indonesian constitution is a rule of law and to make the Indonesian state and its society more advanced.